2016
DOI: 10.3390/min6010021
|View full text |Cite
|
Sign up to set email alerts
|

A Solid State NMR Investigation of Recent Marine Siliceous Sponge Spicules

Abstract: Abstract:The composition of four recent siliceous marine sponge spicules was studied and compared. In particular, multinuclear ( 29 Si, 13 C, 31 P) solid state nuclear magnetic resonance (NMR) allowed the characterization of both the mineral and organic constituents in a non-destructive manner. The silica network condensation was similar for all samples. The organic matter showed a similar pattern but varied in abundance as a function of the sponge group (Hexactinellida or Demospongiae) and sampling conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…In the 31 P MAS NMR spectra, similar modifications as previously described for MMT based SSRF were observed, with the replacement of the well-defined signals by a broad chemical environment, shifted to the orthophosphate region (δ = 2.5 ppm) (Figure Cc), probably involving Mg–O–P bonds. Obviously, the solid state NMR results were in good agreement with the results obtained by PXRD and further evidenced the formation of amorphous materials due to mechanochemical activation by milling. Thermogravimetric analyses (Figure ) were performed for all precursors and milled samples in order to investigate the effect of mechanochemical treatment on composition.…”
Section: Resultssupporting
confidence: 70%
“…In the 31 P MAS NMR spectra, similar modifications as previously described for MMT based SSRF were observed, with the replacement of the well-defined signals by a broad chemical environment, shifted to the orthophosphate region (δ = 2.5 ppm) (Figure Cc), probably involving Mg–O–P bonds. Obviously, the solid state NMR results were in good agreement with the results obtained by PXRD and further evidenced the formation of amorphous materials due to mechanochemical activation by milling. Thermogravimetric analyses (Figure ) were performed for all precursors and milled samples in order to investigate the effect of mechanochemical treatment on composition.…”
Section: Resultssupporting
confidence: 70%
“…The spectral deconvolution allows for calculation of the proportions of these three components, as gathered in Table 2 , made on spectra with a similar signal/noise ratio. The silica condensation degree obtained is representative of an overall well-condensed silica network, in agreement with that was usually obtained for such siliceous sponge material [ 17 , 62 ]. More precisely, D was assessed as 0.92 for the AL and 0.91 for the PG.…”
Section: Resultssupporting
confidence: 88%
“…As a result of 29 Si HPDec-MAS ssNMR and 1 H MAS ssNMR, FTIR and X-ray analyses we demonstrated that the spicules are composed of well condensed silica [cf. 17 , 62 ] with the outermost AL characterized by slightly more condensed silica, with less water, than the rest of the spicule. Etching in NaOH revealed that the silica is permeated by homogenous organics of protein character, most probably collagen, silicatein and/or galectins, as indicated by 13 C CP-MAS ssNMR analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Copyright 2006 Materials Research Society. Reprinted with permission from ref . Copyright 2016 MDPI.…”
Section: Sio2mentioning
confidence: 99%
“…Copyright 2011 Elsevier. Granular core–plain shell particles reprinted with permission from ref . Copyright 2016 MDPI.…”
Section: Sio2mentioning
confidence: 99%